Shock-resistant compression battery electrode with negative Poisson's ratio structure and preparation method of shock-resistant compression battery electrode

By using negative Poisson's ratio structure and in-situ refrigeration technology in lithium-ion battery electrodes, the problems of complexity and poor performance of traditional electrode preparation methods are solved, the excellent deformation ability and electrochemical performance of the electrode are achieved, and the electrode is simplified. Process and reduce costs.

CN119480890AActive Publication Date: 2025-02-18SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411595341.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to maintain excellent mechanical durability and electrochemical performance under deformation, and the traditional electrode preparation method is complex, high cost, and unfriendly to the environment, making it difficult to achieve efficient development of flexible batteries.

Method used

The method of preparing impact compression battery electrodes with negative Poisson's ratio structure is used to mix the active materials, conductive agents, binders and solvents of lithium-ion battery electrodes in a certain proportion, and use in-situ refrigeration technology and molding method to prepare the Multi-scale electrodes with directional holes and bionic structures.

Benefits of technology

The excellent deformation capability and electrochemical performance of the electrode are achieved, the process is simplified and the cost is reduced, and it is suitable for mass production, and the electrode has an adjustable microporous structure, which is suitable for electrode preparation in other battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480890A_ABST
    Figure CN119480890A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of deformation battery energy storage devices, in particular to a preparation method of an anti-impact compression battery electrode with a negative Poisson's ratio structure, which comprises the following steps: mixing a lithium ion battery electrode active material with a conductive agent, a binder and a solvent according to a certain mass ratio to prepare electrode ink; ink is injected into a mold which is manufactured by a 3D printer and has a negative Poisson's ratio structure, and directional freezing is carried out on a copper plate soaked in liquid nitrogen. And finally obtaining the multi-scale electrode with a directional hole structure and a macroscopic negative Poisson's ratio structure on a micro scale through post-treatment such as freeze drying. The electrode with the multi-scale bionic structure has excellent compressibility and can be compressed by 50%. The electrode also has high specific capacity, good cycling stability and rate capability. The method for preparing the deformed electrode through the directional freezing auxiliary mold is low in cost, easy and convenient to operate and wide in application range and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of deformable battery energy storage devices, and in particular to a method for preparing an impact-resistant compression battery electrode with a negative Poisson's ratio structure. Background Art

[0002] The emergence of flexible electronic devices, wearable devices, and implantable medical devices has completely changed people's daily lives, and the demand for high-performance flexible batteries is growing. At present, a major challenge in the development of flexible batteries is to design and quickly and inexpensively manufacture electrodes that can maintain excellent mechanical durability and electrochemical properties under deformation. However, traditional electrode preparation methods are complex, costly, environmentally unfriendly, and have average battery performance, making it difficult to achieve efficient development of flexible batteries. It is difficult to produce thick electrodes using direct writing 3D printing, and the printing success rate is very low, which is inconvenient for mass production. Printing electrodes using a photocuring printer requires mixing the electrode slurry and photosensitive resin in a certain proportion before printing. The content of active substances in the electrodes produced in this way is very low and affects the normal charging and discharging of the battery. Summary of the invention

[0003] The purpose of the present invention is to solve the problems in the background technology and propose a method for preparing a negative Poisson's ratio structure for impact-resistant compression battery electrodes. The lithium-ion battery electrode method proposed in the present invention is novel, simple in process, low in cost, and can realize the arbitrary multi-scale geometry and microstructure of the electrode, which has important application value for the development of high-performance flexible batteries.

[0004] The technical solution of the present invention is a shock-resistant compression battery electrode with a negative Poisson's ratio structure, wherein the shock-resistant compression battery electrode comprises a battery positive electrode and a battery negative electrode;

[0005] The impact-resistant compression battery electrode is a compressible flexible electrode with a negative Poisson's ratio structure of a 3D stereoscopic structure. The macroscopic structure of the electrode includes a double-arrow shape with a negative Poisson's ratio and its derivative shapes; the microscopic structure of the electrode has directional holes, and the directional holes grow from bottom to top to form vertical microchannels that simulate the interior of a plant.

[0006] A method for preparing an impact-resistant compression battery electrode with a negative Poisson's ratio structure, used for preparing the above-mentioned impact-resistant compression battery electrode,

[0007] The specific steps include:

[0008] S1. Mixing the lithium-ion battery electrode active material, the conductive agent, the binder and the solvent in a certain mass ratio, and stirring and grinding the mixture to prepare the electrode ink;

[0009] S2, manufacturing a three-layer demouldable structure mold with a negative Poisson's ratio;

[0010] S3, injecting electrode ink into the assembled mold, using in-situ freezing technology as an aid, placing the mold containing ink on a copper plate immersed in liquid nitrogen to achieve directional freezing;

[0011] S4. The printed electrode is freeze-dried to obtain a multi-scale electrode having a directional pore structure at the micro scale and a macro bionic structure.

[0012] Preferably, the electrode active material in S1 is selected from lithium iron phosphate, lithium manganese oxide, lithium titanate, lithium nickel cobalt manganese oxide or a combination thereof.

[0013] Preferably, the conductive agent in S1 is selected from carbon nanotubes, graphene, carbon black or a combination thereof.

[0014] Preferably, in S1, the binder is selected from cellulose nanofibers, sodium alginate or a combination thereof; and the solvent is water.

[0015] Preferably, the mass ratio of the active material, the conductive agent and the binder in S1 is 4-6:2-4:1-3.

[0016] Preferably, a magnetic stirrer is used for stirring in S1 for 1 to 12 hours to fully mix the ink, and a proper amount of solvent is evaporated by grinding to adjust the viscosity of the ink.

[0017] Preferably, the mold manufacturing method in S2 includes 3D printing, laser cutting, and CNC machine tool processing.

[0018] Preferably, the temperature of the liquid nitrogen copper sheet in S3 ranges from -100°C to -10°C.

[0019] Preferably, the freeze-drying time in S4 is 1 to 12 hours, and the freeze-drying temperature is -10 to -50°C.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] 1. Excellent deformation ability and electrochemical performance: Compared with traditional planar lithium-ion battery electrodes, the preparation method of the lithium-ion battery structure electrode proposed in the present invention can achieve inward contraction of both sides of the electrode during compression deformation while maintaining good electrochemical performance.

[0022] 2. Simplified process and low cost: The present invention provides a mold forming method assisted by directional freezing technology, which has a simple process and low cost and is suitable for mass production.

[0023] 3. Optimized microstructure: Using the vertical microchannels of the tree's internal structure as a bionic model and combining it with directional freezing technology, the preparation of the electrode's microporous structure is achieved, which can shorten the ion transmission distance, promote ion transmission, adapt to volume changes, and improve the electrochemical performance of the battery.

[0024] 4. Adjustable microporous structure: By adjusting the ratio of raw materials, the temperature of directional freezing and the drying time, the electrode prepared by the method of the present invention has an adjustable microporous structure, which can change the number and size of the microporous structure distribution.

[0025] 5. Wide applicability: The method for preparing lithium-ion battery electrodes proposed in the present invention is also applicable to the preparation of electrodes for other battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Figure 3D printed mold with negative Poisson's ratio;

[0027] Figure 2 is the microscopic SEM image of the structured electrode;

[0028] Figure 3 This is a macroscopic structure diagram of an electrode with a negative Poisson's ratio;

[0029] Figure 4 The macroscopic geometric structure diagram of other structure electrodes;

[0030] Figure 5 For structural electrode performance testing Figure 1 ;

[0031] Figure 6 For structural electrode performance testing Figure 2 ;

[0032] Figure 7 This is a test diagram of a battery assembled using electrodes prepared using this scheme to light up an LED lamp. DETAILED DESCRIPTION

[0033] Example 1

[0034] A shock-resistant compression battery electrode with a negative Poisson's ratio structure, the preparation method of which comprises the following steps:

[0035] 1. Lithium iron phosphate, carbon nanotubes, cellulose nanofibers and water were mixed in a mass ratio of 5:3:2, stirred for 12 hours and then ground to a suitable viscosity to prepare printing electrode ink.

[0036] 2. Use a light-curing 3D printer to make a double-arrow three-layer demoldable structure mold with a negative Poisson's ratio.

[0037] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0038] 4. The printed electrode is freeze-dried (-40°C) to obtain a double-arrow-shaped electrode with a directional pore structure at the microscopic level and a negative Poisson's ratio at the macroscopic level.

[0039] Example 2

[0040] A grid structured impact-resistant compression battery electrode, the preparation method of which comprises the following steps:

[0041] 1. Mix lithium nickel cobalt manganese oxide (NCM811), PVDF (dissolved in NMP), and few-layer graphite in a mass ratio of 8:1:1, stir for 12 hours, and then grind to a suitable viscosity to prepare printing electrode ink.

[0042] 2. Use a light-curing 3D printer to make a three-layer demoldable structure mold of the grid structure.

[0043] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0044] 4. The printed electrodes are freeze-dried (-40°C) to obtain electrodes with microscopic directional pore structures and macroscopic grid structures.

[0045] Example 3

[0046] An impact-resistant compression battery electrode with a brick wall structure, the preparation method of which comprises the following steps:

[0047] 1. Mix micron silicon powder, carbon black, sodium alginate and water in a mass ratio of 2:1:1, stir for 12 hours and grind to a suitable viscosity to prepare printing electrode ink.

[0048] 2. Use a light-curing 3D printer to make a three-layer demoldable structural mold with a brick wall structure.

[0049] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0050] 4. The printed electrodes are freeze-dried (-40°C) to obtain electrodes with microscopic directional pore structures and macroscopic brick wall structures.

[0051] Example 4

[0052] A honeycomb structured impact-resistant compression battery electrode, the preparation method of which comprises the following steps:

[0053] 1. The sulfur-carbon composite powder, graphene, cellulose nanofibers and water were mixed in a mass ratio of 7:2:1, stirred for 12 hours and then ground to a suitable viscosity to prepare a printed electrode ink.

[0054] 2. Use a light-curing 3D printer to make a three-layer removable structure mold of a honeycomb structure.

[0055] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0056] 4. The printed electrodes are freeze-dried (-40°C) to obtain electrodes with microscopic directional pore structures and macroscopic honeycomb structures.

[0057] Example 5

[0058] A shock-resistant compression battery electrode with a negative Poisson's ratio structure, the preparation method of which comprises the following steps:

[0059] 1. Lithium titanate, carbon nanotubes, cellulose nanofibers and water were mixed in a mass ratio of 5:3:2, stirred for 12 hours and then ground to a suitable viscosity to prepare a printed electrode ink.

[0060] 2. Use a light-curing 3D printer to make a concave hexagonal three-layer demoldable structure mold with a negative Poisson's ratio.

[0061] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0062] 4. The printed electrode is freeze-dried (-40°C) to obtain a concave hexagonal structure electrode with a directional pore structure at the microscopic level and a negative Poisson's ratio at the macroscopic level.

[0063] Example 6

[0064] An impact-resistant compression battery electrode of a corrugated paper structure, the preparation method of which comprises the following steps:

[0065] 1. Lithium iron phosphate, carbon nanotubes, cellulose nanofibers and water were mixed in a mass ratio of 2:1:1, stirred for 12 hours and then ground to a suitable viscosity to prepare printing electrode ink.

[0066] 2. Use a light-curing 3D printer to make a three-layer demoldable structural mold of corrugated paper structure.

[0067] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0068] 4. The printed electrodes are freeze-dried (-40°C) to obtain electrodes with microscopic directional pore structures and macroscopic corrugated paper structures.

[0069] Example 7

[0070] A shock-resistant compression battery electrode with a negative Poisson's ratio structure, the preparation method of which comprises the following steps:

[0071] 1. Lithium iron phosphate, carbon nanotubes, cellulose nanofibers and water were mixed in a mass ratio of 6:3:1, stirred for 12 hours and then ground to a suitable viscosity to prepare printing electrode ink.

[0072] 2. Use a light-curing 3D printer to make an elliptical three-layer demoldable structure mold with a negative Poisson's ratio.

[0073] 3. Inject the electrode ink into the assembled mold, use in-situ freezing technology as an aid, and place the mold containing the ink on a copper plate immersed in liquid nitrogen to achieve directional freezing.

[0074] 4. The printed electrode is freeze-dried (-40°C) to obtain an elliptical structure electrode with a directional pore structure at the microscopic level and a negative Poisson's ratio at the macroscopic level.

[0075] The performance of the electrodes prepared in Examples 1-7 was tested.

[0076] Deformation ability test steps:

[0077] First, the electrodes produced in Examples 1-7 are placed on a compression testing machine, the distance is slowly reduced, and a static compression test is performed on the electrodes; then, the test value when the printed electrode completely recovers to its original state without macroscopic damage when the external force is released is taken as the deformation capacity value; the test records are taken three times respectively and the average value is taken; further, finite element analysis (FEA) is carried out using finite element software to study the strain behavior of the structural electrode under various deformation states.

[0078] Electrochemical performance test steps:

[0079] The printed electrodes and commercial lithium foil were directly used as electrodes, the separator was Celgard 2500, and the electrolyte was 1M LiPF6. The button cells were assembled in an argon-filled glove box and sealed with a hydraulic crimper; the electrochemical performance tests and electrochemical data were collected using the LAND detection system.

[0080] The test results are shown in the following table:

[0081] Table 1 Example parameters and electrode performance

[0082]

[0083]

[0084] Analysis of the experimental data in Table 1 shows that the deformation capacity of the double-arrow-negative Poisson's ratio structure electrode is tested, and the maximum range can achieve 50% compression deformation. When the maximum compression is 25%, it can be completely restored to its original state after the external force is released, without any macroscopic damage. Finite element analysis was performed on the electrode, and the maximum strain under the above deformation conditions was less than the final strain of the material. This shows that the electrode prepared by this method can achieve compression while maintaining good electrochemical properties. The positive and negative electrodes of the double-arrow-negative Poisson's ratio structure are made according to the method of Example 1, and the LED lamp can be lit when placed in a soft-pack battery, and the brightness of the LED does not change significantly under compression.

[0085] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. An impact-resistant compression battery electrode with a negative Poisson's ratio structure, characterized in that: The impact-resistant compression battery electrode comprises a battery positive electrode and a battery negative electrode; The impact-resistant compression battery electrode is a compressible flexible electrode with a negative Poisson's ratio structure of a 3D stereoscopic structure. The macroscopic structure of the electrode includes a double-arrow shape with a negative Poisson's ratio and its derivative shapes; the microscopic structure of the electrode has directional holes, and the directional holes grow from bottom to top to form vertical microchannels that simulate the interior of a plant.

2. A method for preparing an impact-resistant compression battery electrode with a negative Poisson's ratio structure, used to prepare the impact-resistant compression battery electrode according to claim 1, characterized in that: The specific steps include: S1. Mixing the lithium-ion battery electrode active material, the conductive agent, the binder and the solvent in a certain mass ratio, and stirring and grinding the mixture to prepare the electrode ink; S2, manufacturing a three-layer demouldable structure mold with a negative Poisson's ratio; S3, injecting electrode ink into the assembled mold, using in-situ freezing technology as an aid, placing the mold containing ink on a copper plate immersed in liquid nitrogen to achieve directional freezing; S4. The printed electrode is freeze-dried to obtain a multi-scale electrode having a directional pore structure at the micro scale and a macro bionic structure.

3. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: The electrode active material in S1 is selected from lithium iron phosphate, lithium manganese oxide, lithium titanate, lithium nickel cobalt manganese oxide or a combination thereof.

4. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: The conductive agent in S1 is selected from carbon nanotubes, graphene, carbon black or a combination thereof.

5. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: In S1, the binder is selected from cellulose nanofibers, sodium alginate or a combination thereof; and the solvent is water.

6. The method for preparing an impact-resistant compression battery electrode with a negative Poisson's ratio structure according to any one of claims 2 to 5, characterized in that: The mass ratio of active material, conductive agent and binder in S1 is 4-6:2-4:1-3.

7. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: During the stirring in S1, a magnetic stirrer is used for 1 to 12 hours to fully mix the ink, and a proper amount of solvent is evaporated by grinding to adjust the viscosity of the ink.

8. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: The mold making methods in S2 include 3D printing, laser cutting, and CNC machine tool processing.

9. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: The temperature of the liquid nitrogen copper sheet in S3 ranges from -100°C to -10°C.

10. The method for preparing a shock-resistant compression battery electrode with a negative Poisson's ratio structure according to claim 2, characterized in that: The freeze drying time in S4 is 1 to 12 hours, and the freeze drying temperature is -10 to -50°C.

Citation Information

Patent Citations

  • 3D printing stretched yarn, processing method and application

    CN108248018A

  • Flexible negative-Poisson-ratio component and preparation method and application thereof

    CN113334758A

  • Stretchable electrode and preparation method and application thereof

    CN118676316A

  • Lithium ion battery bionic structure deformation electrode prepared based on 3D printing technology

    CN118888682A